2009
DOI: 10.1177/0192623308330790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Exposure to Crack Cocaine on the Respiratory Tract of Mice

Abstract: Smoked cocaine (crack cocaine) causes several forms of injury to the respiratory tract, including asthma exacerbations, lung edema and hemorrhage, and nasal mucosal alterations. Few studies, however, have assessed respiratory tract pathology in habitual users of crack cocaine. Here, we describe the histological alterations in the respiratory tract of mice caused by chronic inhalation of crack cocaine. Twenty 2-month-old BALB/c mice were exposed to the smoke of 5 g crack cocaine in an inhalation chamber once a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
0
9
0
4
Order By: Relevance
“…Indeed, a dose of 5 g of crack cocaine inhaled by the mice promotes a serum concentration of cocaine that would be similar to a nonlethal (safe for the cardiovascular system) dose of 0.69 to 1.37 mg/kg insufflated cocaine (Collins et al, 2007). Even in nonlethal doses there are pulmonary histological alterations in animals such as hemorrhage, nose and bronchial epithelium atrophy and macrophagic inflammation in the same exposure system that we use (Herculiani et al, 2009). The entrance of the crack cocaine in the body is inhaled (absorption by lungs) and that is why this drug is very addictive when compared to the injected or nosed cocaine, thus demonstrating that the dose applied in our study is consistent with a dose administered by users.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, a dose of 5 g of crack cocaine inhaled by the mice promotes a serum concentration of cocaine that would be similar to a nonlethal (safe for the cardiovascular system) dose of 0.69 to 1.37 mg/kg insufflated cocaine (Collins et al, 2007). Even in nonlethal doses there are pulmonary histological alterations in animals such as hemorrhage, nose and bronchial epithelium atrophy and macrophagic inflammation in the same exposure system that we use (Herculiani et al, 2009). The entrance of the crack cocaine in the body is inhaled (absorption by lungs) and that is why this drug is very addictive when compared to the injected or nosed cocaine, thus demonstrating that the dose applied in our study is consistent with a dose administered by users.…”
Section: Discussionmentioning
confidence: 96%
“…The negative pressure allowed the use of less drug than required by other devices, and exposure to the smoke of 250 mg of crack cocaine achieved similar plasma cocaine concentrations as reported by Herculiani et al (2009) andPires et al (2012).…”
Section: Discussionmentioning
confidence: 64%
“…The main problems of the existing apparatus include the complexity of drug burning and smoke exposure (Boni, Barr, & Martin, 1991;Burchfield, Abrams, Miller, & DeVane, 1991;He, Lidow, & Lidow, 2006) and the large amount of drug that is required to perform the experiment (Herculiani et al, 2009). Therefore, this study developed an inexpensive and easily assembled apparatus for smoke exposure of inhaled drugs that requires small drug amounts that are safe for the researcher.…”
Section: Introductionmentioning
confidence: 99%
“…This study was an attempt to define the relationship of airway wall thickening with the severity of SII patients using chest CT in the early phase after injury [13]. An animal experimental study showed that the bronchial wall in mice with SII was expected to swell and be thicker than that in the control animals [14], and a correlation was also reported between bronchial wall thickness and airway narrowing using virtual bronchoscopy in a swine model [10]. However, no reports have evaluated this bronchial wall swelling with clinical data except in animal experiments [15].…”
Section: Discussionmentioning
confidence: 99%